Analysis of Problems in Managing the Innovative Development of Secondary Education in Modern Russia - Olga V. Rogach; Tatyana M. Ryabova; Elena V. Frolova (National Research Mordova State University, 2017)
Introduction: the article deals with the transition of secondary education to an innovative way of development. Enhancing the effectiveness of management of this process in the context of the sociocultural transformation of Russian society is one of the pressing problems. The article describes a comprehensive analysis of managing practices employed in innovative development of secondary education, and also identifies and characterises the key problems of this field. Materials and Methods: the authors chose the secondary schools of Moscow as an object of research. The study included a survey of teachers and parent community, interviews with heads of educational institutions and representatives of the district education directorates of Moscow. Results: the study revealed that currently there is no clearly defined social and individual demand for educational services. The creation of an innovative environment would reduce the destructive consequences of introducing innovations into the practice of modern secondary schools. Parents of schoolchildren support the need to modernise the existing education system to increase its innovative potential. The essence of their expectations remains very traditional. This is the enrollment of the school graduates in universities. At the same time, they highlight a number of shortcomings of current innovations: increased burden on parents and schoolchildren, high resource costs, and lack of adequate organisational and pedagogical support for innovations introduced in school education. Therefore, it is relevant to use the mechanism of social partnership in the practice of managing innovative processes. Discussion and Conclusions: the potential of the Russian education system is blocked by a multitude of problems and inconsistencies of its elements. The situation is aggravated by weak influence of parents on schools' governance processes, by the general distrust of people in the actions of authorities, and the lack of effective technologies for managing the innovative development of school education. The results of the research have a practical application for managers of educational organisations, teachers and parents of schoolchildren. Some provisions and conclusions can be applied to developing the educational institutions and optimising the interaction between schools and universities.